Penyuluhan Kesehatan Tentang Pentingya Pemberian Imunisasi Lanjutan/ Booster (DPT-HB-Hib dan Campak) pada Balita di Wilayah Kerja Puskesmas Leupung Kabupaten Aceh Besar - Faradilla Safitri; Fauziah Andika; Cut Asiah (JURNAL PENGABDIAN KEPADA MASYARAKAT BIDANG KESEHATAN, 2020)
Abstract           Toddler is a general term for children aged 1-3 years (toddler) and preschool children (3-5 years). When the child is toddlers, begin to be given further immunization or booster immunization. Advanced immunization is a repeat of basic immunization to maintain the level of immunity and to extend the optimal protection period from further immunization and this is only obtained if the child has received complete basic immunization. About 1.5 million children in the world die each year because of diseases that can be prevented by immunization. The coverage of children under five who received further immunization / booster (DPT-HB-Hib and measles) in 2019 is 75.95%. This figure has met the 2019 Strategic Plan target of 70%. However, 50% of the provinces are still unable to achieve the target. One of the provinces with the lowest coverage is Aceh (26.91%). Puskesmas Leupung is one of the health centers in Aceh Besar District, based on 2019 data, the coverage of advanced immunization is still below UCI standards (below 80%).          Community Service Activities are a form of the contribution of Ubudiyah Faculty of Health Sciences lecturers in the implementation of higher education tridharma. This activity is also expected to improve health status. The service that has been carried out in this activity is in the form of health counseling with the theme "The Importance of Provision of Advanced Immunization / Booster (DPT-HB-Hib and Measles) to Toddlers". This health counseling was carried out in the work area of the Leupung Puskesmas, Aceh Besar District, which consists of 3 posyandu points, namely in Pulot Village on Thursday, July 16 2020, Deah Mamplam Village on Tuesday, July 21 2020 and in Meunasah Mesjid Village on Friday, 24 July 2020, which was held at 10.00 WIB until completion, the total number of mothers who attended this health counseling time was 46 people. The implementation of this health education is in collaboration with the Leupung Health Center, Aceh Besar District. Keywords: toodler, Advanced immunization/ booster